2018
DOI: 10.1111/scd.12299
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia due to macroglossia in a patient with amyloidosis associated with multiple myeloma: A case report

Abstract: Amyloidosis is a group of heterogeneous conditions characterized by the deposition of extracellular proteinaceous substances called amyloids. The diagnosis is usually confirmed after a particular body organ has been affected. However, oral manifestations have been identified in 39% of affected patients. Systemic amyloidosis may be primary or in association with multiple myeloma and typically affecting elder adults. The diagnosis of amyloidosis is usually associated with clinical features with histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
(11 reference statements)
0
5
0
1
Order By: Relevance
“…Macroglossia can arise from many different etiologies, including amyloidosis. Amyloidosis is a group of diseases that share the feature of the deposition of an extracellular proteinaceous substance referred to as amyloid [6]. Approximately 39% of patients with amyloidosis exhibit oral manifestations, with the tongue being the most common site [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Macroglossia can arise from many different etiologies, including amyloidosis. Amyloidosis is a group of diseases that share the feature of the deposition of an extracellular proteinaceous substance referred to as amyloid [6]. Approximately 39% of patients with amyloidosis exhibit oral manifestations, with the tongue being the most common site [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The simplified classification of systemic amyloidosis includes: primary amyloidosis (AL), which is the most common type of amyloidosis and it is associated with multiple myeloma; secondary amyloidosis (AA), which is associated with chronic infections or inflammatory diseases, such as rheumatoid arthritis; Aβ 2 M associated with long‐term haemodialysis; familial ATTR amyloidosis, an inherited disease with mutant form of transthyretin (TRR); localized amyloidosis, in which amyloid deposits are usually due to local production of immunoglobulin light chains not originating from the bone marrow (Guijarro‐Martínez et al, 2009). Macroglossia is observed in more than 40% of amyloidosis cases and it may be an unique early manifestation of the disease (da Costa et al, 2018; Guijarro‐Martínez et al, 2009). However, localized amyloidosis of the tongue is rare and it's often secondary to a systemic form (Guijarro‐Martínez et al, 2009).…”
Section: Diagnosismentioning
confidence: 99%
“…Several reports demonstrated that dysphagia in DMD patients is associated with dystrophic changes in muscles related to mastication [ 36 ]. Macroglossia, which is common in DMD patients [ 28 , 37 ], is defined as an enlarged tongue and is often associated with dysphagia [ 5 ]. Therefore, preventing the deterioration of mastication and swallowing functions in DMD is important to improve the patient’s quality of life.…”
Section: Introductionmentioning
confidence: 99%